Rorty against Rorty: climate change, rug-pulling, and the rhetoric of philosophy - Gaskill, N (Duke University Press, 2022)
As the leading contribution to the Common Knowledge symposium “Whatever Happened to Richard Rorty?,” this essay asks why Rorty was so often taken to be saying things that he claimed he was not. The argument is that Rorty’s rhetorical approach and jargon engendered this confusion and undermined his effectiveness as a philosopher and public intellectual. The focus here is on two points: first, on how, in his eagerness to shut down attempts to claim a privileged path to Reality, he gave the impression of dismissing not only hierarchies but also distinctions; and second, on how his separation of causes and reasons retained a dualism of the “one world, many perspectives” model that elsewhere he rejected. This essay concludes that leading figures of science studies at the present time, notably Bruno Latour, Isabelle Stengers, and Donna Haraway, better equip readers to move past the feeling of deprivation that comes from shedding centuries- old philosophical assumptions and that their explicit rejection of the nature/culture binary makes their work better suited to addressing the great problem of our time — climate change.